Penguatan Promosi Kesehatan melalui Literasi Kesehatan pada Santri - Harpiana Rahman; Syamsul Alam; Arfandi Ahmad; Fahri Bachmid; Achdian Anggreni Bangsawan; Achmad Nadhil Edar; Ramdaniyah Ramdaniyah (Idea Pengabdian Masyarakat, 2021)
Based on data from the Ministry of Communication and Information, recorded there were 1,028 fake news or hoaxes about health information spread since 2020 on social media platforms. Data shows that 73.7% of the 27 4.9 million people in Indonesia are internet users This condition makes it difficult to control the infodemic in Indonesia. Digital Data 2021 states that around 170 million people are active users of social media. Health literacy socialization is an effort to build awareness among teenagers in filtering the right health information.